Venous thromboembolism in adults treated for acute lymphoblastic leukaemia: Effect of fresh frozen plasma supplementation - Lauw, Mandy N.; van der Holt, Bronno; Middeldorp, Saskia; Meijers, Joost C. M.; Cornelissen, Jan J.; Bajetta, Mariateresa; Biemond, Bart J. (Thrombosis and Haemostasis, 2013)
Treatment of acute lymphoblastic leukaemia (ALL) is frequently complicated by venous thromboembolism (VTE). The efficacy and optimal approach of VTE prevention are unclear, particularly in adult patients. We assessed the effect of thromboprophylaxis on symptomatic VTE incidence in cycle 1 of ALL treatment in adult patients. Secondly, we explored potential etiologic factors for VTE and the clinical impact of VTE on ALL outcome. We retrospectively assessed symptomatic VTE incidence and use of thromboprophylaxis in 240 adults treated for newly diagnosed ALL in the Dutch-Belgian HOVON-37 multicentre study (1999–2005). Potential etiologic factors were explored by analysis of patient and disease characteristics, impact of VTE on ALL outcome by analysis of complete remission and overall survival rates. Symptomatic VTE was observed in 24 of 240 patients (10%). Thromboprophylaxis differed by centre (prophylactic fresh frozen plasma (FFP) supplementation or no thromboprophylaxis) and was applied only during L-asparaginase in cycle 1. VTE incidence was significantly lower with FFP supplementation than without FFP (6% vs. 19%; adjusted odds ratio [OR] 0.28; 95% confidence interval [CI] 0.10–0.73). FFP did not influence antithrombin or fibrinogen plasma levels. Patients with VTE in cycle 1 had a significantly poorer complete remission rate (adjusted OR 0.18; 95% CI 0.07–0.50), particularly patients with cerebral venous thrombosis (adjusted OR 0.17; 95% CI 0.04–0.65). Our study suggests that prophylactic FFP supplementation effectively reduces symptomatic VTE incidence during ALL treatment in adults. This should be confirmed in a randomised controlled trial.
Keywords: Acute lymphoblastic leukaemia; fresh frozen plasma; L-asparaginase; thromboprophylaxis; venous thrombosis